The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1529-8817.2011.01032.x
|View full text |Cite
|
Sign up to set email alerts
|

FREQUENT CLONALITY IN FUCOIDS (FUCUS RADICANS AND FUCUS VESICULOSUS; FUCALES, PHAEOPHYCEAE) IN THE BALTIC SEA1

Abstract: Asexual reproduction by cloning may affect the genetic structure of populations, their potential to evolve, and, among foundation species, contributions to ecosystem functions. Macroalgae of the genus Fucus are known to produce attached plants only by sexual recruitment. Recently, however, clones of attached plants recruited by asexual reproduction were observed in a few populations of Fucus radicans Bergström et L. Kautsky and F. vesiculosus L. inside the Baltic Sea. Herein we assess the distribution and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 63 publications
8
74
0
Order By: Relevance
“…Extraction of DNA, PCR reactions and microsatellite analyses were done following the description in [24]. The software STRUCTURE [25] was used to assign individuals into genetically coherent groups, and GENCLONE [26] was used to identify clones among the Baltic Sea individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Extraction of DNA, PCR reactions and microsatellite analyses were done following the description in [24]. The software STRUCTURE [25] was used to assign individuals into genetically coherent groups, and GENCLONE [26] was used to identify clones among the Baltic Sea individuals.…”
Section: Methodsmentioning
confidence: 99%
“…DNA extractions were carried out following the procedure described in Johannesson et al (2011). Following, five microsatellite loci developed from Fucus species (Engel et al 2003) were genotyped and genotyping reactions and conditions have also been previously described in Johannesson et al (2011).…”
Section: Genetic Analysismentioning
confidence: 99%
“…Following, five microsatellite loci developed from Fucus species (Engel et al 2003) were genotyped and genotyping reactions and conditions have also been previously described in Johannesson et al (2011). Allele sizes were determined on a Beckman-Coulter automated sequencer using CeqMan 8000 software (Beckman-Coulter).…”
Section: Genetic Analysismentioning
confidence: 99%
“…These analyses also emphasized that Baltic populations of most investigated species were genetically strongly differentiated from North Sea and Atlantic populations. The observed patterns of differentiation and reduced genetic diversity are considered to be caused by geographic isolation, environmental selection pressures [17], and vestigilization of sexuality and clonality [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the high degree of genetic endemism and the reduced genetic variation found in these key organisms e.g. [22], [23] may negatively affect their response to environmental change [19]. In contrast to macroscopic organisms, very little is known to date about the population structure of Baltic planktonic microorganisms.…”
Section: Introductionmentioning
confidence: 99%